The tao of Bruce Lee : a martial arts memoir - Miller, Davis (Nerw York Harmony Books, 2000)
Combining biography and personal memoir, this portrait of a great martial arts master explores the life of the man who began as an obscure Hong Kong actor and now occupies iconic stature in American culture
Baker & Taylor, 8/2000
Keywords: Lee, Bruce, 1940-1973; Martial artists--United States--Biography; Actors--United States--Biography; Tao--Miscellaneous; Memoir